Acquired hemophilia A: Updated review of evidence and treatment guidance. Issue 7 (5th June 2017) - Kruse‐Jarres, Rebecca; Kempton, Christine L.; Baudo, Francesco; Collins, Peter W.; Knoebl, Paul; Leissinger, Cindy A.; Tiede, Andreas; Kessler, Craig M.
Abstract: Acquired hemophilia A (AHA) is a rare disease resulting from autoantibodies (inhibitors) against endogenous factor VIII (FVIII) that leads to bleeding, which is often spontaneous and severe. AHA tends to occur in elderly patients with comorbidities and is associated with high mortality risk from underlying comorbidities, bleeding, or treatment complications. Treatment, which consists of hemostatic management and eradication of the inhibitors, can be challenging to manage. Few data are available to guide the management of AHA‐related bleeding and eradication of the disease‐causing antibodies. Endorsed by the Hemostasis and Thrombosis Research Society of North America, an international panel of experts in AHA analyzed key questions, reviewed the literature, weighed the evidence and formed a consensus to update existing guidelines. AHA is likely underdiagnosed and misdiagnosed in real‐world clinical practice. Recommendations for the management of AHA are summarized here based on the available data, integrated with the clinical experience of panel participants.